Proyecto de factibilidad para la exportación de rosas al mercado ruso. - Acosta Puga, Freddy Fernando (2014)
The objectives of the Ecuadorian flower is to increase its profits and this can get it is through the search for new markets economically independent; for this reason the objective of this project is to enter markets with opportunities for the export of roses to the Russian market. The Russian market is an interesting opportunity for the location of roses given the existence of high product demand dates, which would benefit the organization obtaining safe sales annually. The Russian market demands is willing to pay higher prices for roses provided the product is of high quality giving you competitive advantage to the Ecuadorian product on the Chinese and Colombian.